The Competitiveness Development Of Shanghai Port Industry In The Context Of Government Support Strategies - Yanling, Guo; Yizhou, Zeng (Migration Letters, 2024)
This quantitative study investigates the development of competitiveness in the Shanghai port industry, with a focus on the impact of government support strategies. The research constructs and tests a structural equation model based on 13 hypotheses related to organizational flexibility (OFY), government support (GST), industrial organizational structure (SIO), organizational innovation (OIN), management innovation (MIN), and port industry competitiveness (CPI). The study utilizes a range of statistical analyses, including reliability tests, convergent validity tests, structural model fit assessments, and mediation analyses. Results reveal that organiz[1]ational flexibility (OFY), government support (GST), and industrial organizational structure (SIO) significantly contribute to port industry competitiveness (CPI). Additionally, organizational innovation (OIN) and management innovation (MIN) play crucial roles in enhancing competitiveness. The study emphasizes the intricate relationships among these factors, illustrating a complex network that influences the competitiveness of the Shanghai port industry. This research provides empirical evidence and insights for industry practitioners, policymakers, and scholars, offering a comprehensive understanding of the dynamics involved in the competitiveness development of the Shanghai port industry within the framework of government support strategies. In conclusion, the study sheds light on the critical interplay among organizational flexibility (OFY), government support (GST), industrial organizational structure (SIO), organizational innovation (OIN), management innovation (MIN), and port industry competitiveness (CPI). The intricate relationships within this complex network highlight the multifaceted nature of factors influencing the competitiveness of the Shanghai port industry. The findings underscore the pivotal roles of government support strategies and organizational flexibility in fostering innovation, contributing to a nuanced understanding of the dynamics shaping the sustained development of competitiveness in the Shanghai port industry. This research serves as a valuable resource for industry practitioners, policymakers, and scholars, offering empirical evidence and comprehensive insights into the intricate landscape of the Shanghai port industry’s competitiveness.